1998
DOI: 10.1038/sj.bmt.1701319
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of extramedullary relapse of AML after busulfan/cyclophosphamide conditioning and allogeneic stem cell transplantation

Abstract: Summary:While allogeneic stem cell transplantation (SCT) is curative for a significant number of patients with AML, relapse of disease within the bone marrow and/or extramedullary (EM) sites following high-dose therapy continues to limit the success of this treatment. Between October 1985 and December 1996, 81 adults underwent allogeneic SCT for de novo AML at our centre. Fortytwo patients remain alive and free of leukaemia with a median follow-up of 50 months. The 5-year actuarial event-free survivals (EFS) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 21 publications
5
39
3
Order By: Relevance
“…Extramedullary relapse with or without bone marrow involvement accounted for 41% (14/34) of overall initial relapse. Our results are consistent with other recent data that reported an overall frequency of extramedullary relapse ranging from 5 to 12% of all patients 7,20 and the percentage of extramedullary relapse with or without concomitant relapse in the bone marrow among the overall relapse of 27-50%. [5][6][7] The discrepancy of reported frequency of extramedullary relapse may be due to under-reporting in retrospective registry data and the longer survival of patients in recent series due to less patients dying of transplantation-related causes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Extramedullary relapse with or without bone marrow involvement accounted for 41% (14/34) of overall initial relapse. Our results are consistent with other recent data that reported an overall frequency of extramedullary relapse ranging from 5 to 12% of all patients 7,20 and the percentage of extramedullary relapse with or without concomitant relapse in the bone marrow among the overall relapse of 27-50%. [5][6][7] The discrepancy of reported frequency of extramedullary relapse may be due to under-reporting in retrospective registry data and the longer survival of patients in recent series due to less patients dying of transplantation-related causes.…”
Section: Discussionsupporting
confidence: 83%
“…This remarkable effect is due to the graft-versus-leukemia (GVL) effect that occurs after allogeneic HCT. Although the overall frequency of acute leukemia relapse is less after allogeneic HCT, a high proportion of extramedullary relapses [4][5][6][7] in extremely diverse sites has been reported, including the brain, [8][9][10][11] head and neck, [8][9][10]12 gastrointestinal tract, 13 breast, 14,15 liver, 9 pancreas, 16 urogenital tract, 13,17 spinal canal and paravertebral tissue, 8 bone and periosseous tissue, 13,14,18 pleura, 14 pericardium, 9 peritoneum, 19 and skin. 20 The median time from allogeneic HCT to acute leukemia relapse was longer in cases with extramedullary relapse with or without bone marrow involvement when compared to cases of bone marrow only relapse.…”
mentioning
confidence: 99%
“…Our finding is consistent with the data of Simpson et al 14 who reported a similar frequency of extramedullary relapse (45% of all relapses) with or without bone marrow involvement among 81 patients with AML. In both studies, patients received the BuCy regimen for preparation for BMT.…”
Section: Discussionsupporting
confidence: 83%
“…This is relatively high compared to the largest reported series and also contrasts with the very low incidence of EM relapse of AML following standard-dose chemotherapy. [4][5][6]9 Bone was the most common site of EM relapse, although many different sites were affected. Previously reported cases included almost all conceivable locations.…”
Section: Discussionmentioning
confidence: 99%
“…5 Two reports, however, suggest a higher prevalence in patients with relapsed AML post alloBMT; Mortimer et al 4 noted an EM component in 20% of 95 patients and Simpson et al 6 described EM relapse in 10 of 22 patients.…”
mentioning
confidence: 99%